2021
DOI: 10.1016/j.jbc.2021.100475
|View full text |Cite
|
Sign up to set email alerts
|

Ectopically expressed olfactory receptors OR51E1 and OR51E2 suppress proliferation and promote cell death in a prostate cancer cell line

Abstract: Olfactory receptors (ORs), the largest family of G protein–coupled receptors, are expressed in the nasal epithelium where they mediate the sense of smell. However, ORs are also found in other non-nasal tissues, but the role of these ectopic ORs in cell signaling, proliferation, and survival is not well understood. Here, using an inducible expression system in the lymph node carcinoma of the prostate (LNCaP) cell line, we investigated two ectopic ORs, OR51E1 and OR51E2, which have been shown to be upregulated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…While our data and that of others suggest a proliferative, anti-apoptotic role for ORs, other studies are consistent with a tumor suppressing role for members of this family. Thus, ectopically expressed OR51E1 and OR51E2 suppressed prostate cancer cells growth in association with the upregulation of cytostatic and cell death markers, including p27, p21 and p53, and enhanced annexin V staining [46]. Taken together, ORs display organ-specific, concentration-dependent bioactivities.…”
Section: Discussionmentioning
confidence: 85%
“…While our data and that of others suggest a proliferative, anti-apoptotic role for ORs, other studies are consistent with a tumor suppressing role for members of this family. Thus, ectopically expressed OR51E1 and OR51E2 suppressed prostate cancer cells growth in association with the upregulation of cytostatic and cell death markers, including p27, p21 and p53, and enhanced annexin V staining [46]. Taken together, ORs display organ-specific, concentration-dependent bioactivities.…”
Section: Discussionmentioning
confidence: 85%
“…OR1A2 is expressed in HuH7 cells, and it is sensitive to (-)-citronellal and citronellol [ 46 ]. LNCaP cells express OR51E1 and OR51E2 (also named prostate-specific G-protein-coupled receptor [PSGR]), which recognize β-ionone, propionic acid, butyric acid, and nonanoic acid [ 47 , 48 ]. As HepG2, HuH7, and LNCaP have not been widely utilized as functional expression systems for GPCRs, we first screened several experimental conditions, such as transfection reagents and culture buffers, based on the responsiveness of OR1A1 ( S1 Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…The full spectrum of their ligands is still unknown, but deorphanization efforts showed that they can be activated by lactate, butyric acid, propionic acid, and other aliphatic acids. 23 The activation of OR51E2 by the ligand beta-ionone leads to inhibition of prostate cancer cell proliferation, by blocking the AR nuclear translocation. 21 However, Sanz et al showed that beta-ionone stimulation of OR51E2 in LNCaP cells promotes a PI3K-gamma-dependent increase in tumor invasiveness and metastatic potential.…”
Section: Introductionmentioning
confidence: 99%
“…53 In addition, changes in OR51E2 expression have been associated with activation of nuclear factor-kappa B and protein kinases. 23 OR51E2 is expressed in normal prostate epithelial tissue, which suggests that it might play a physiological role. 54 Moreover, experiments have shown that the activation of OR51E1 inhibits cell proliferation and induces senescence in prostate cancer.…”
Section: Introductionmentioning
confidence: 99%